Wannier-Mott excitons in alkali metal-based nitridorhenate: A DFT study. (December 2022) - Vijay, A.; Hariharan, M.; Sneha, G.; Eithiraj, R.D.
Abstract: To better understand the electronic, structural, optical, and transport properties of the alkali metal-based nitridorhenate (Li5 ReN4 ), first-principles calculations were performed using the full potential linearized augmented plane wave (FP-LAPW) method within the generalised gradient approximation (GGA) framework. The ground-state properties were computed for an orthorhombic structure (Pmmn-59). Both the band structure and the total density of states were carried out. Based on the band structure, the Li5 ReN4 compound is a direct band semiconductor with a bandgap value of 2.68 eV. In addition, the optical properties were calculated, indicating that lithium nitridorhenate is a highly absorbent material. The effective masses of the electrons and holes were calculated. Also, we investigate the connection between exciton binding energy and band structure. Moreover, the exciton for Li5 ReN4 is a weak exciton of the Mott-Wannier type. Furthermore, the transport properties were investigated using the semi-classical Boltzmann theory as implemented in the BoltzTraP code. Owing to its semiconducting nature, the material has a high Seebeck coefficient (S) of 287 μV/K at 300 K. At 300 K and 400 K, the predicted thermoelectric figure of merit was 0.790 and 0.802. Each of these results shows that our compound is a strong choice for applications in photovoltaic, optoelectronic, and thermoelectrical devices. Additionally, based on the observation of thermoelectric figure of merit, the Li5 ReN4 compound is also suitable for waste heat regeneration or waste heat recovery process. Graphical Abstract: The calculated charge density distribution of Li5 ReN4 along (011). ga1